Plasmaspheric Hiss: Coherent and Intense. Issue 12 (5th December 2018) - Tsurutani, Bruce T.; Park, Sang A.; Falkowski, Barbara J.; Lakhina, Gurbax S.; Pickett, Jolene S.; Bortnik, Jacob; Hospodarsky, George; Santolik, Ondrej; Parrot, Michel; Henri, Pierre; Hajra, Rajkumar
Abstract: Intense ~300‐Hz to 1.0‐kHz plasmaspheric hiss was studied using Polar plasma wave data. It is found that the waves are coherent in all local time sectors with the wave coherency occurring in approximately three‐ to five‐wave cycle packets. The plasmaspheric hiss in the dawn and local noon time sector are found to be substorm (AE*) and storm (SYM‐H*) dependent. The local noon sector is also solar wind pressure dependent. It is suggested that coherent chorus monochromatic subelements enter the plasmasphere (as previously suggested by ray tracing models) to explain these plasmaspheric hiss features. The presence of intense, coherent plasmaspheric hiss in the local dusk and local midnight time sectors is surprising and more difficult to explain. For the dusk sector waves, either local in situ plasmaspheric wave generation or propagation from the dayside plasmasphere is possible. There is little evidence to support substorm generation of the midnight sector plasmaspheric hiss found in this study. One possible explanation is propagation from the local noon sector. The combination of high wave intensity and coherency at all local times strengthens the suggestion that the electron slot is formed during substorm intervals instead of during geomagnetic quiet (by incoherent waves). Plasmaspheric hiss is found to propagate at all angles relative to the ambient magnetic field, θkB . Circular, elliptical, and linear polarized plasmaspheric hiss have been detected. No obvious, strong relationship between the wave polarization and θkB was found. This information of hiss properties should be useful in modeling wave‐particle interactions within the plasmasphere. Plain Language Summary: Plasmaspheric hiss is found to be coherent (at all local times). The coherency occurs in packets of ~3 to 5 cycles. For the dawn and noon local time sectors, a scenario of substorm and solar wind pressure generation of outer zone chorus with further propagation into the plasmasphere is supported by the data analysis results. The predominant wave polarization of hiss is found to be elliptical, with some minor presence of circular and linear polarizations. This is in general agreement with theoretical expectations.The presence of intense, coherent plasmaspheric hiss strongly supports the new hypothesis that the electron slot is formed during substorms rather than geomagnetic quiet periods. The loss of relativistic E ~ 1MeV electrons for the inner magnetosphere (L > 6) may be due to wave‐particle interactions with coherent plasmaspheric hiss. Key Points: Intense plasmaspheric hiss is coherent at all local times Approximately 3 to 5 cycle coherent plasmaspheric hiss are outer zone chorus subelements that have propagated into the plasmasphere Most of plasmaspheric hiss is elliptically polarized with some circular and linear polarizations; these features are consistent with theory